Annual Report on the Working of State Electricity Boards & Electricity Departments June 2001 - Planning Commission (Planning Commission, 2001)
This Chapter gives an overall view of the Report and highlights some of the important parameters and crucial issues relating to the power sector in the country. The subsequent chapters bring out detailed analysis of various issues and large variations in the performance of SEBs and EDs. Chapter 2 gives details of the plan outlays and expenditure in the power sector, distribution of power sector outlay between various activities viz. generation, transmission & distribution (T&D), renovation and modernisation etc. and also gives the power balances as well as the elasticity of electricity generation and consumption with respect to the GDP. In Chapter 3, physical performance of the SEBs and EDs is reviewed
Power & Energy Division Planning Commission
Power & Energy Division Planning Commission